Spirobifluorene-based oligopyridine derivatives as electron-transporting materials for green phosphorescent organic light-emitting diodes - Guo, Xuan; Lv, Fang; Zhao, Zifeng; Gu, Jiannan; Qu, Bo; Xiao, Lixin; Chen, Zhijian (ORGANIC ELECTRONICS, 2020)
The electron-transporting materials (ETMs), 2,7-bis(3,5-di (pyridin-3-yl)phenyl)-9,9'-spirobi [fluorene] (3-4PySF) and 2,7-bis(3,5-di (pyridin-4-yl)phenyl)-9,9'-spirobi [fluorene] (4-4PySF) were designed and synthesized by combining spirobifluorene moiety with di(pyridine-3-yl)phenyl and di(pyridine-4-yl)phenyl, respectively. The spimbifluorene moiety improves materials' rigid twisted structure to ensure the morphological stability of amorphous film, and pyridine acts as electron acceptor to enhance electron-transporting ability of materials. The dependence of electron-transporting property on the position of substituted pyridine rings was studied. The melting point (T-m) of 4-4PySF is estimated to be 41 degrees C higher than that of 3-4PySF. And the higher current density in the electron only devices exhibited by 4-4PySF revealed the effect of nitrogen atom position on the charge-transporting properties. Green PhOLEDs based on bis(2-phenylpyridine)iridium (III) (2,2,6,6-tetramethylheptane-3,5-diketonate) (Ir (ppy)(2)tmd) as the emitter and 3-4PySF, 4-4PySF and 1,3,5-tris(N-phenylbenzimid azol-2-yl-benzene (TPBi) as ETMs were fabricated. Compared to the device based on the conventional ETM TPBi, the devices based on new ETMs exhibited a higher maximum external quantum efficiency (EQE) of 20.5% and a lower turn-on voltage (V-on) of 2.6 V.